Heritage language preservation among migrant children in Poznań and Wrocław: The emic and etic perspective - Sugay, Larysa; Goździak, Elżbieta M. (Glottodidactica, 2024)
Children in migrant families are often torn between maintaining their heritage language and acquiring fluency in the language of the country where they reside. Knowledge of the majority language helps them succeed in school and find meaningful employment, while the ability to speak the heritage language facilitates communication within their families. However, acquiring competencies in both languages is not always easy. It is especially complicated in multigenerational families, and families where the parents speak different heritage languages. In schools, the dynamics differ depending on the number of speakers of particular heritage languages. In this paper, we analyse the dynamics within families and schools of children with at least one foreignborn parent. We ask who is responsible for the children’s facility with either or both languages and analyse ways of integration and exclusion of migrant children vis-à-vis the language/s they choose to speak. We explore these questions within grounded theory to identify emic and etic attitudes towards majority / minority languages. The empirical data come from ethnographic research with migrant children and their families, teachers, and teachers’ intercultural assistants conducted in Poznań and Wrocław.